2021
DOI: 10.21203/rs.3.rs-783177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MYB Transcription Factor Family in Sweet Cherry (Prunus avium L.): Genome-wide Investigation, Evolution, Structure, Characterization and Expression Patterns

Abstract: Back groundMYB Transcription factors (TFs) are most imperative and largest gene family in plants, which participate in development, metabolism, defense, differentiation and stress response. The MYB TFs has been studied in various plant species. However, comprehensive studies of MYB gene family in the sweet cherry (Prunus avium L.) are still unknown. ResultsIn the current study, a total of 69 MYB genes were investigated from sweet cherry genome and classified into 28 subfamilies (C1-C28 based on phylogenetic an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…It is worth noting that within the same subfamily, the exon/ intron patterns of R2R3-CnMYB genes showed remarkable, with the majority of genes having no more than two introns. This finding aligns with previous research that also observed the presence of a maximum of two introns in most plant R2R3-MYB genes (Sabir et al, 2022;Yin et al, 2022). Furthermore, we analyzed the motif compositions of CnMYB proteins.…”
Section: Gene Structure and Protein Motif Analysis Of R2r3-myb Genes ...supporting
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that within the same subfamily, the exon/ intron patterns of R2R3-CnMYB genes showed remarkable, with the majority of genes having no more than two introns. This finding aligns with previous research that also observed the presence of a maximum of two introns in most plant R2R3-MYB genes (Sabir et al, 2022;Yin et al, 2022). Furthermore, we analyzed the motif compositions of CnMYB proteins.…”
Section: Gene Structure and Protein Motif Analysis Of R2r3-myb Genes ...supporting
confidence: 90%
“…Our findings revealed that the majority of MYB proteins contained motifs 1, 2, 3, 4, 5, and 6 (Figure 4), while most MYB proteins contained motifs 1, 3, 5, and 8 in Dendrobium catenatum (Zhang et al, 2021). The majority of MYB genes, included several motifs (1, 2, 3, 4, and 5) in Prunus avium (Sabir et al, 2022). These motifs were conserved within specific subgroups, and proteins in the same subgroup that share these motifs likely (Qin et al, 2023).…”
Section: Gene Structure and Protein Motif Analysis Of R2r3-myb Genes ...mentioning
confidence: 66%
“…As TFs, MYB proteins are mostly localized in the nucleus, where they play a crucial role in regulating downstream gene expression. Nevertheless, some MYB proteins were localized in the cytoplasm, mitochondria, or endoplasmic reticulum, and their roles in these organelles need to be further elucidated (Avila et al, 1993;Zhang et al, 2021;Sabir et al, 2022). Our results showed that all IaMYB proteins were localized in the nucleus.…”
Section: Discussionmentioning
confidence: 73%
“…The loss/gain of intron position and length is slow, so intron positions can often retain information about gene homology [41]. Many studies of exon/ intron structure have shown that most members in the same subfamily have similar exon numbers and different exon and intron lengths [42,43]. In this study, we found that the number of exons/introns in group A, B, and C was exactly equal, and most of the gene structures in group F, G, and H were similar, while some genes (such as JrPP2C04, JrPP2C07, and JrPP2C41) are quite different from other genes (such as JrPP2C37, JrPP2C19, and JrPP2C25) (Figs.…”
Section: Discussionmentioning
confidence: 99%